2022
DOI: 10.1186/s12905-022-01705-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between mass media exposure and endorsement of HIV-infected female teachers' teaching: insight from 2014 Ghana Demographic and Health Survey

Abstract: Introduction Ghana recorded 19,931 new annual HIV infections in 2018 translating to 14,181 AIDS-related deaths. Mass media is capable of ensuring the sustainability of initiatives aimed at curbing HIV/AIDS epidemic by reducing HIV/AIDS stigma and discrimination. The study aimed at exploring if mass media plays a role in whether HIV-infected female teachers should be allowed to teach in Ghana. Materials and methods The study used women’s file of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Sexually active women who were not exposed to mass media had higher odds of indulging in risk factors for HIV compared to those exposed to mass media. The study ndings are consistent with a study in Ghana which reported a reduction in risky sexual behaviour among people who had a TV or radio in their homes [43]. This may be because the HIV/AIDS organizations and the Ministry of Health, Rwanda disseminate HIV information via newspapers, radio, and TV [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sexually active women who were not exposed to mass media had higher odds of indulging in risk factors for HIV compared to those exposed to mass media. The study ndings are consistent with a study in Ghana which reported a reduction in risky sexual behaviour among people who had a TV or radio in their homes [43]. This may be because the HIV/AIDS organizations and the Ministry of Health, Rwanda disseminate HIV information via newspapers, radio, and TV [19].…”
Section: Discussionsupporting
confidence: 89%
“…This may be because the HIV/AIDS organizations and the Ministry of Health, Rwanda disseminate HIV information via newspapers, radio, and TV [19]. Therefore, media should be explored further with more innovative strategies to continue providing adequate knowledge about HIV prevention and control which enables adopting appropriate attitudes and practices to an even wider audience [19,43].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research, conducted by Nketiah-Amponsah et al (2018) and Appiah et al (2022), has shed light on the individual impacts of education and wealth on HIV-related knowledge and attitudes among women in Ghana [ 18 , 19 ]. Research has indicated a correlation between increased levels of education and greater wealth with enhanced knowledge about HIV and more favorable attitudes towards the virus [ 18 , 19 ]. Nevertheless, an area that has received limited attention is the possible interaction between educational attainment and wealth in influencing the HIV outcomes of women in Ghana [ 7 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, wealth refers to the ability to obtain and utilize various assets and opportunities. There is a positive correlation between a woman’s level of wealth and her ability to access healthcare services, such as HIV testing, counseling, and treatment [ 18 , 19 ]. The attainment of economic stability can equip individuals with the resources to access reliable information from diverse sources, including educational programs, community initiatives, and healthcare professionals [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the total fertility rate of Ghana, which is 4.2 children per woman, 30 parity was recoded as ‘one birth’, ‘two births’, ‘three births’ and ‘four or more births’. Following 32 computation of access to mass media from 3 cardinal variables (ie, frequency of reading newspapers/magazines; frequency of listening to the radio; and frequency of watching television), we categorised mass media into ‘yes’ and ‘no’. Women’s household decision-making autonomy recoded as ‘not autonomous’ and ‘autonomous’; sex of the household head recoded as ‘male’, and ‘female’; partner’s education recoded as ‘no formal education’, and ‘formal education’; and zone of residence recoded as ‘coastal zone’, ‘middle zone’ and ‘savanna zone’.…”
Section: Methodsmentioning
confidence: 99%